International Legal and National Legal Regulation of Participation of Political Parties and Citizens in the Election Process - BAZAROVA, Gulmira; BADANOVA, Marzhan; BALGIMBEKOVA, Gulnara; SMAGULOVA, Rizagul; BORAGARIN, Ruslan; MUSIN, Kuat (Journal of Advanced Research in Law and Economics, 2018)
The article discusses the role of international electoral standards in the formation of national electoral legislation. The essence, meaning and main sources of international election standards are disclosed. Based on the analysis of existing international standards, the content and importance of electoral standards for the formation of the national electoral legislation of the Republic of Kazakhstan and foreign countries are disclosed and the issues of enforcement and compliance are raised. The analysis of the electoral legislation, the recommendations of the OSCE Mission to improve the electoral legislation of the Republic of Kazakhstan and foreign countries.